1978
DOI: 10.1136/jnnp.41.10.940
|View full text |Cite
|
Sign up to set email alerts
|

Recovery in hydrocephalic dementia after shunt operation.

Abstract: SUM MARY Twenty-three patients with hydrocephalic dementia were studied before and after shunt operation, and improvement was found in 12. Before operation, the improved cases showed more symptoms of confabulation, gait disturbance, urinary incontinence, lack of insight, and constructional apraxia. The improvement was also most marked in these symptoms. The significance of general versus specific symptoms, duration, and aetiology is discussed from a differential diagnostic standpoint, and we conclude that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
21
1
8

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 31 publications
(41 reference statements)
10
21
1
8
Order By: Relevance
“…We found signifi cant improvement in verbal memory and recall and psychomotor speed and motor precision after shunt surgery, but performance on the Stroop Color-Word test did not improve, suggesting that impairment of some executive functions may not be relieved by shunt. This corroborates fi ndings that frontal lobe executive functions may be impaired early in NPH patients, with irreversible damage to the frontostriatal pathways [4,5,27] . Improvement in another task of executive function, the Trail making B test (which relies more on sequencing and task switching), was seen in fewer than half of our patients, albeit the Trail making test is not specifi c for frontal lobe dysfunction [28] .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We found signifi cant improvement in verbal memory and recall and psychomotor speed and motor precision after shunt surgery, but performance on the Stroop Color-Word test did not improve, suggesting that impairment of some executive functions may not be relieved by shunt. This corroborates fi ndings that frontal lobe executive functions may be impaired early in NPH patients, with irreversible damage to the frontostriatal pathways [4,5,27] . Improvement in another task of executive function, the Trail making B test (which relies more on sequencing and task switching), was seen in fewer than half of our patients, albeit the Trail making test is not specifi c for frontal lobe dysfunction [28] .…”
Section: Discussionsupporting
confidence: 76%
“…[2] . NPH may account for up to 5% of causes of dementia [3] , and the cognitive defi cits are of 'frontosubcortical' type [4][5][6] . There is decline in active retrieval of memory, executive functions and complex information processing; visuospatial perception and visuoconstructive skills may also be affected [3,7] .…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with Gustafson and Hagberg's findings [9], who noted a pronounced postoperative improvement from a marked dysfunction in "spatioperceptual performance" preoperatively .…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, there is no consensus regarding diagnostic criteria and preoperative tests, although there have been several attempts to identify such factors. For instance, known cause or short history are stressed by some authors as potent predictors [3,9,11,151. Bgirgesen and Gjerris [6] have recently shown that a combination of clinical features, computed tomography (CT) findings, recording of intraventricular pressure, and measurement of conductance to outflow of cerebrospinal fluid (C,,,) may result in an improved success rate following shunting.…”
mentioning
confidence: 99%
“…30 The duration of preoperative symptoms has been reported to be a significant factor in the prognosis of NPH. 16,30 Patients with sNPH present with a shorter duration of preoperative symptoms, because the presence of a known etiology can lead to an earlier investigation and detection of NPH symptoms. Similarly, Thomsen et al reported that patients with NPH of a known cause had a better outcome than patients with iNPH, and that disease duration of less than 12 months was an important factor for successful outcome.…”
Section: 5mentioning
confidence: 99%